Determinants of employee performance: the mediating role of job satisfaction in competence, motivation, and work environment model - Tria Maulia; Suhardi Suhardi; Rahmad Firdaus (Lembaga Riset Mutiara Akbar (LARISMA), 2026)
This study aims to analyze the influence of competence, work motivation, and work environment on employee performance with job satisfaction as a mediating variable. This study uses a quantitative approach with Structural Equation Modeling Partial Least Squares (SEM-PLS) analysis. The research sample was 100 formal sector employees in the Bangka Belitung Islands Province. Data were collected using a questionnaire with a Likert scale. The results showed that competence did not significantly influence performance or job satisfaction. The work environment significantly influenced job satisfaction, but did not influence performance. Work motivation significantly influenced performance, but did not influence job satisfaction. Job satisfaction had a positive and significant effect on employee performance and was the variable with the largest influence. These findings indicate that improving employee performance is more effectively done through increasing motivation and job satisfaction supported by a conducive work environment. This study provides an empirical contribution to the human resource management literature regarding the mediating role of job satisfaction in improving employee performance.